Radiographic and plantar pressure assessment of pes planovalgus severity in children with cerebral palsy. (May 2021) - Look, Nicole; Autruong, Patrick; Pan, Zhaoxing; Chang, Frank M.; Carollo, James J.
Abstract: Background: Pes planovalgus is common in children with cerebral palsy. Although severity influences treatment, there still lacks standard clinical measurements to objectively quantify pes planovalgus in this population. The comparison of pedobarographic data and radiographic measurements to clinical evaluation has not been reported in this population. Methods: 395  feet were identified from a population of ambulatory pediatric patients with cerebral palsy. Each patient initially underwent clinical evaluation by an experienced physical therapist who classified feet as: 136 controls, 116 mild, 100 moderate, and 43 severe pes planovalgus. Quantitative measurements were then calculated from antero-posterior and lateral radiographs of the foot. Pedobarographic analysis included the arch index, center of pressure index, and a newly defined medial index. Findings: A multivariate analysis was performed on the radiographic and pedobarographic measurements collected. It identified seven variables that improved objective classification of pes planovalgus severity when utilized together. These include the foot progression angle, initial contact force, arch index, medial index, antero-posterior talonavicular coverage, lateral calcaneal pitch and lateral Meary's angle. While the lateral calcaneal pitch angle statistically differed amongst all severity classes, no pedobarographic value statistically differed between all severity classes. Interpretation: Overall, the combination of radiographic and pedobarographic measurements provides valuable information for objectively classifying severity of pes planovalgus in children with cerebral palsy by utilizing these values together rather than independently. In a clinical setting, radiographs and pedobarographic data may be obtained to enhance assessment of severity and guide treatment. Highlights: Radiographs and pedobarographs objectively assess pes planovalgus in children with Cerebral Palsy. Variables from both modalities distinguish pathology from control. Multivariate analysis identified 7 indices that improve clinical severity classification.